Arbaʻah ḥiburim teʼologiyim - Luther, Martin, 1483-1546 (Magnes - Ḳlasiḳah, 2018)
Martin Luther, the initiator of the Protestant Reformation, presents the principles of his theological and political theory in the four treatises before us. In the first essay from 1917, also known as Ninety-Five Theses, Luther condemns the Catholic custom of selling plenary indulgences, already expressing insinuated criticism against the Catholic Church and Pope for their pretentions attempts to mediate between the believer and God. In the three essays he wrote in 1520, Luther undermines the foundations of the Catholic Church and its medieval development. This approach had a tremendous influence on all countries that later became Protestant.